The architect's guide to small firm management - Klein, Rena M. (Hoboken, New Jersey : John Wiley & Son, Inc., 2010)
The definitive guide to management success for sole practitioners and leaders of small design firms Owning and operating a small architectural design firm can be challenging, with tight project deadlines, on-the-fly meetings, rush proposals, and fluctuating workloads as part of the firm$1 (Bs day-to-day activities. To help small firm owners cope with the chaos and prepare for the unexpected, here is The Architect$1 (Bs Guide to Small Firm Management, a no-nonsense guide to repurposing daily demands into workable, goal-directed solutions. Crucial topics such as self-aware leadership, people management, technology, financial health, scenario planning, sustainable practice, and future trends are examined using real-life case studies and business model paradigms. This definitive text explores the whole system experience of a small firm practice to deliver organizational strategies proven to keep a firm$1 (Bs creative mission on a steady, productive path. The Architect$1 (Bs Guide to Small Firm Management addresses how small firm owners can: Deal effectively with unexpected circumstances and shifting work requirements Meet the demands of the marketplace while creating a satisfying workplace Set and achieve goals in an environment of constant change This book is a must-have for those facing the often harsh reality of managing small design firms in a difficult and changing economy. Entrepreneurial architects and designers will discover how to define their own personal and professional meanings of success, as well as how to refocus their business approach to replace long, unrewarding hours with manageable, satisfying ones.s
Acknowledgments -- Introduction -- Chapter 1. Bringing order out of chaos -- Chapter 2. Whole firm system -- Chapter 3. Routinize the routine -- Chapter 4. Leadership matters -- Chapter 5. Lifecycle of a small firm -- Chapter 6. Transition times -- Chapter 7. Financial management: beyond intuition -- Chapter 8. Scenario planning -- Chapter 9. Strategic thinking -- Chapter 10. Small design firm practice models -- Chapter 11. Technology and integrated practice in small firms -- Chapter 12. Big-picture trends -- Chapter 13. Sustainable economics -- Index.
"The American Institute of Architects."
Includes bibliographical references and index.
Keywords: ARCHITECTURAL PRACTICE